Terms of the contract - . Teacher Abbas Fadel Abbas; Dr. Ali Fawzi Ibrahim al-Mousawi (The college of law and political science journal, 2023)
The idea of the contract requirement is one of the issues that occupy an important aspect of the dispute in legal jurisprudence. As the word jurists do not agree on what is meant by this word. The idea of ​​the contract requirement may mean the basic obligation arising from the contract. Or, according to the expression of the Muslim jurists, By this they mean the main obligation in the contract. If we wanted, we would say that it means the essence of the contract, However, the contract may include, in addition to the main obligation arising from the nature of the contract, There are other obligations as a result of the terms agreed upon in the contract. On this basis, the idea of the contract requirement does not have an agreed upon meaning. This research is an attempt to study the concept of the contract requirement by studying the legal position of the laws being compared.